2001
DOI: 10.1046/j.1462-2920.2001.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate‐dependent iron(II) oxidation in paddy soil

Abstract: Iron(III) profiles of flooded paddy soil incubated in the greenhouse indicated oxidation of iron(II) in the upper 6 mm soil layer. Measurement of oxygen with a Clark-type microelectrode showed that oxygen was only responsible for the oxidation of iron(II) in the upper 3 mm. In the soil beneath, nitrate could be used as electron acceptor instead of oxygen for the oxidation of the iron(II). Nitrate was still available 3 mm below the soil surface, and denitrifying activity was indicated by higher concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(71 citation statements)
references
References 70 publications
2
68
0
1
Order By: Relevance
“…However, vertical geochemical profiles of Campus Lake sediment contained coexisting nitrate and dilute HCl-extractable Fe(II) concentrations. The coexistence of ambient nitrate and Fe(II) concentrations is not restricted to Campus Lake sediments, as similar geochemical profiles have been observed in rice paddy soil cores (40). The aforementioned thermodynamic predictions do not account for dynamic microbial metabolic processes generating nitrate.…”
Section: Discussionmentioning
confidence: 64%
“…However, vertical geochemical profiles of Campus Lake sediment contained coexisting nitrate and dilute HCl-extractable Fe(II) concentrations. The coexistence of ambient nitrate and Fe(II) concentrations is not restricted to Campus Lake sediments, as similar geochemical profiles have been observed in rice paddy soil cores (40). The aforementioned thermodynamic predictions do not account for dynamic microbial metabolic processes generating nitrate.…”
Section: Discussionmentioning
confidence: 64%
“…Until this report, only the above two Pseudogulbenkiania strains had been reported (16,28); however, our results suggest that these bacteria may be ubiquitous in rice paddy soils. Since reduced metals and fertilizer-N are available in paddy soils, the Pseudogulbenkiania strains obtained in this study may play a role in nitrate-dependent Fe(II)-oxidation, the reaction previously observed in rice paddy soils (21). More studies are necessary to determine if our Pseudogulbenkiania strains can oxidize metals in combination with nitrate reduction.…”
Section: Denitrifying Properties Of the Strainsmentioning
confidence: 58%
“…On the other hand, the rhizosphere Fe(II) oxidation in paddy soils may be due to other biotic processes. For example, nitrate-reduction coupled to Fe(II) oxidation was reported in the rice paddy soil (Ratering and Schnell, 2001). The ubiquity and diversity of these anaerobic FeOB suggests that nitrate-dependent Fe(II) oxidation, light-independent reactions, have the potential to contribute to anoxic Fe oxidation in the rhizosphere, provided adequate concentrations of a suitable electron acceptor.…”
Section: A Rhizosphere Fe Cyclementioning
confidence: 99%